Investigation on Mechanical Properties of MAR-M247 Superalloy for Turbine Blades by Experiment and Simulation - Hao Lin; Haipeng Geng; Xifeng Zhou; Leiming Song; Xiaojun Hu (Archives of Metallurgy and Materials)
This study aimed to investigate the metallographic structure and the impact of the heat treatment process on the MAR-M247 superalloy, a high-temperature nickel-based superalloy commonly used in turbine blades. The heat treatment process can potentially influence the mechanical properties of the MAR-M247 superalloy at different temperatures. A strength simulation analysis of gas turbine blades should include the variations in the mechanical properties of the material. The effect of heat treatment on grain size was investigated by metallographic experiments, and numerical calculations of material mechanical properties were conducted. The mechanical property parameters necessary for finite element analysis of turbine blades were determined. Finally, a finite element simulation model of the blade was established based on these mechanical property parameters, and strength analysis was performed. The simulation results provided the stress distribution and the strength of the turbine blade.